The Development of Coherent Speech in Elementary School Students in The Process of Constructive and Artistic Activity - Budak, Valerii (2020)
The article examines the development of speech in elementary school students. The research objective is to determine the status of coherent speech development in 3rd-grade students in the process of constructive and artistic activity. The article defines the criteria (structural and compositional, communicative and productive, and communicative and creative), indicators, and levels of development of coherent speech in elementary school students in the process of constructive and artistic activity. Each criterion includes a group of qualitative content-disclosing indicators and characterizes the achievements of students in the intended type of activity. Based on this, the authors have developed a methodological tool that allows them to diagnose coherent speech development in 3rd-grade students in the process of constructive and artistic activity and to conduct a precise quantitative differentiation by high, sufficient, medium, and low levels of coherent speech formation with specific characteristics for qualitative measurements that open up prospects for the development of appropriate effective measures for improving the quality of training students for such activity.